Prediksi Kelulusan Mahasiswa Stikom Tunas Bangsa Prodi Sistem Informasi Dengan Menggunakan Algoritma C4.5 - Lydia Yohana Lumban Gaol; M. Safii; Dedi Suhendro (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2021)
Graduation is an important element in an accreditation assessment process of an institution or university. It is important to find out information about the predictions of student graduation in the Information Systems Study Program at STIKOM Tunas Bangsa Pematangsiantar, so that students who cannot graduate on time can be identified earlier. The application of data mining can be used to predict student graduation. Method that often used to predict student graduation is classification method. This research using C4.5 Algorithm. Data that used as training data are from alumni of Information Systems Study Program at STIKOM Tunas Bangsa and the final level student data of Information Systems Study Program at STIKOM Tunas Bangsa used as testing data. Through this research, it is expected that the results can provide information on predictions of student graduation on time and as a suggestion for the university in making good decisions for improvement in the future.